2018
DOI: 10.1002/app.46532
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐triggered poly(siloxane‐urethane)s based on disulfide bonds for self‐healing application

Abstract: Polydimethylsiloxane (PDMS) is one of the most widely employed silicon‐based polymers for its high flexibility, low usage temperature, excellent water resistance, outstanding electrical insulting property, and physiological inert, etc. However, the covalent‐bonded SiO bonds are unable to heal automatically when damaged, which would result in the failure of the materials and devices. Disulfide bond based polymers show high healing efficiency at moderate temperature and have been investigated intensively. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…38 Positions of different peaks for neat PU and PU/CNC nanocomposites were similar. 40 Sharp peaks at around 2930 and 2850 cm −1 were related to asymmetric and symmetric stretching vibrations of alkyl groups. 34 This showed that the reaction medium was completely free of moisture and all isocyanate groups have formed urethane groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…38 Positions of different peaks for neat PU and PU/CNC nanocomposites were similar. 40 Sharp peaks at around 2930 and 2850 cm −1 were related to asymmetric and symmetric stretching vibrations of alkyl groups. 34 This showed that the reaction medium was completely free of moisture and all isocyanate groups have formed urethane groups.…”
Section: Resultsmentioning
confidence: 99%
“…In HS0.0, endothermic peak at 174.7 C was related to T m,HS . 40 On the other hand, the first stage was related to destruction of HS which had lower thermal stability than SS due to lower molecular weight. The existence of the HS crystals in the polymer demonstrated high phase separation between the HS and SS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extrinsic self‐healing materials require healing agents during the healing process . Although intrinsic self‐healing materials can undergo self‐healing process multiple times through dynamic noncovalent interactions (such as hydrogen bonds and π–π stacking) and dynamic covalent bonds(such as dynamic boroxine bonds, DA bonds and urea bonds). Self‐healing materials based on dynamic covalent bonding have advantages such as high strength, increased thermal stability, and solvent resistance compared to self‐healing materials based on noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%